A pragmatic approach to the use of inotropes for the management of acute and advanced heart failure: An expert panel consensus. (15th December 2019) - Farmakis, Dimitrios; Agostoni, Piergiuseppe; Baholli, Loant; Bautin, Andrei; Comin-Colet, Josep; Crespo-Leiro, Maria G.; Fedele, Francesco; García-Pinilla, Jose Manuel; Giannakoulas, George; Grigioni, Francesco; Gruchała, Marcin; Gustafsson, Finn; et al.
Abstract: Inotropes aim at increasing cardiac output by enhancing cardiac contractility. They constitute the third pharmacological pillar in the treatment of patients with decompensated heart failure, the other two being diuretics and vasodilators. Three classes of parenterally administered inotropes are currently indicated for decompensated heart failure, (i) the beta adrenergic agonists, including dopamine and dobutamine and also the catecholamines epinephrine and norepinephrine, (ii) the phosphodiesterase III inhibitor milrinone and (iii) the calcium sensitizer levosimendan. These three families of drugs share some pharmacologic traits, but differ profoundly in many of their pleiotropic effects. Identifying the patients in need of inotropic support and selecting the proper inotrope in each case remain challenging. The present consensus, derived by a panel meeting of experts from 21 countries, aims at addressing this very issue in the setting of both acute and advanced heart failure. Highlights: Inotropes increase cardiac output mainly by enhancing cardiac contractility. Inotropes indicated for heart failure are beta-agonists, milrinone, levosimendan. Inotropes should only be used in low-output acute or advanced heart failure. Identifying patients with low-output heart failure is often challenging. Inotrope selection should be individually tailored.